Thermal Stability and Monomer Elution of Bulk Fill Composite Resins Cured from Different Irradiation Distances - Elmira Jafari Navimipour; Fatemeh Pournaghi Azar; Sajjad Keshipour; Saba Nadervand (Tehran University of Medical Sciences, 2021)
Objectives: This study aimed to evaluate the thermal stability and monomer elution of bulk fill composite resins cured at different irradiation distances. Materials and Methods: Forty cylindrical-shaped (3×4mm) specimens were fabricated from two composite resins (X-tra fil, X-tra base) and cured from 0 and 7mm distances. In 9 specimens, the degree of conversion was determined by the release of monomers. For this purpose, after curing of composites, they were immersed in 5 mL of 99.9% methanol and stored at 37°C for 24h. The eluted monomer was then analyzed by gas chromatography (GC). Also, thermal stability of one sample from each group was assessed by thermogravimetric analysis (TGA) at a rate of 10°C/min. Data were analyzed using two-way ANOVA and Tukey's post-hoc test (P<0.05). Results: X-tra fil had significantly higher degree of conversion than X-tra base (P=0.001). Specimens cured at 7mm distance had significantly lower degree of conversion compared with those cured at 0 mm distance (P=0.001). The interaction effect of composite type and distance of light curing unit from the surface of samples was statistically significant (P=0.001). Regarding the TGA results, the lowest and the highest percentages of weight loss were detected in X-tra fil cured at 0 mm distance and X-tra base cured at 7mm distance, respectively. Conclusion: X-tra fil composite cured at 0mm distance had the highest degree of conversion and thermal stability, and X-tra base composite cured at 7mm distance had the lowest values.